Saving for Development How Latin America and the Caribbean Can Save More and Better - Inter-American Development Bank (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
Why should people - and economies - save? This book on the savings problem in Latin America and the Caribbean suggests that, while saving to survive the bad times is important, saving to thrive in the good times is what really counts. People must save to invest in health and education, live productive and fulfilling lives, and make the most of their retirement years. Firms must save to grow their enterprises, employ more workers in better jobs, and produce quality goods. Governments must save to build the infrastructure required by a productive economy, provide quality services to their citizens, and assure their senior citizens a dignified, worry-free retirement. In short, countries must save not for the proverbial rainy day, but for a sunny day - a time when everyone can bask in the benefits of growth, prosperity, and well-being. This book is open access under a CC BY-NC-ND 3.0 IGO license.